(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The article presents the agrochemical description of colmatage pale gray soils formed in the Isfayramsoy cone spread, in which the total nitrogen is 0.015-0.11% in the case where humus is 1.20-1.31% in plowed layers